Bimbingan Karier di Era Digital: Tantangan dan Peluang bagi Konselor - Apriani Apriani; Arianto Arianto; Ali Irbar; Muh. Syamsir Husein; Ulfa Anisyah Agustina (Journal of Innovative and Creativity, 2026)
The rapid development of digital technology has brought significant changes to the world of work, directly affecting career guidance practices. This condition requires career counselors to adapt by integrating digital technology into their professional services. This study aims to analyze the challenges and opportunities of career guidance in the digital era and their implications for counselors’ competencies. The research employs a qualitative approach using a systematic literature review method of national and international scholarly articles published between 2019 and 2026. Data sources were obtained from Google Scholar, ERIC, SINTA, and Scopus databases. Data analysis was conducted through data reduction, thematic exploration, and synthesis of findings. The results indicate that the main challenges of career guidance in the digital era include gaps in counselors’ digital competencies, difficulties in maintaining the quality of counseling relationships in online services, privacy and ethical issues, and the phenomenon of information overload experienced by clients. On the other hand, digital technology offers significant opportunities to improve service accessibility, time flexibility, and data-based personalization of career guidance. This study concludes that an effective approach to career guidance in the digital era requires a balanced integration of digital technology and a humanistic counseling approach. Therefore, strengthening counselors’ digital competencies and continuous professional development are essential.